2004
DOI: 10.2214/ajr.183.1.1830065
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension: CT of the Chest in Pulmonary Venoocclusive Disease

Abstract: On the initial pretreatment chest CT scan, the presence of ground-glass opacities (particularly with a centrilobular distribution), septal lines, and adenopathy are indicative of pulmonary venoocclusive disease in patients displaying pulmonary hypertension. Caution should be exercised before vasodilator therapy is initiated in the patients whose scans show such radiologic abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
150
0
18

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 246 publications
(177 citation statements)
references
References 24 publications
8
150
0
18
Order By: Relevance
“…High-resolution CT scanning is the investigation of choice. Typical findings suggestive of PVOD are the presence of subpleural thickened septal lines, centrilobular ground-glass opacities (contrasting with a panlobular distribution found in IPAH) and mediastinal lymphadenopathy [54]. The association of these three findings was found to be 100% specific for PVOD in cases of PAH, with a 66% sensitivity [54].…”
Section: Pulmonary Veno-occlusive Disease and Pulmonary Capillary Haementioning
confidence: 94%
“…High-resolution CT scanning is the investigation of choice. Typical findings suggestive of PVOD are the presence of subpleural thickened septal lines, centrilobular ground-glass opacities (contrasting with a panlobular distribution found in IPAH) and mediastinal lymphadenopathy [54]. The association of these three findings was found to be 100% specific for PVOD in cases of PAH, with a 66% sensitivity [54].…”
Section: Pulmonary Veno-occlusive Disease and Pulmonary Capillary Haementioning
confidence: 94%
“…Respiratory auscultatory crackles may occur in PVOD patients with predominant pulmonary infiltrates but the precise prevalence is unknown [7,10]. Pleural effusions have been suggested to be more frequent in PVOD, however, the studies focused on radiography with high-resolution computed tomography (HRCT) of the chest show a similar proportion of pleural effusions in both diseases [8,10,48,49]. Hemoptysis has been described in PVOD; however, in our recent study, hemoptysis was reported infrequently and equally in both idiopathic PAH and PVOD, confirming that alveolar hemorrhage in PVOD is generally occult [8,50].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In contrast, the chest radiograph in PVOD may show significant abnormalities with Kerley B lines or signs of pulmonary edema, most frequently occurring after initiation of pulmonary vasodilator therapy [6,8,10,48,67]. HRCT of the chest may also help to discriminate PVOD and PAH in less acute situations [8,10,48,49] (Figure 3). It has been clearly demonstrated that HRCT in PVOD was characterized by a higher frequency of centrilobular ground-glass opacities, septal lines and mediastinal lymph node enlargement Review as compared with idiopathic PAH [49].…”
Section: High-resolution Computed Tomography Of the Chestmentioning
confidence: 99%
See 2 more Smart Citations